Six new dammarane-type triterpenes from acidic hydrolysate of the stems-leaves of Panax ginseng and their inhibitory–activities against three human cancer cell lines. (September 2015) - Ma, Li-Yuan; Yang, Xiu-Wei
Graphical abstract: Highlights: Triterpenes in acidic hydrolysates of the stems-leaves of Panax ginseng were studied. Six new and 13 known compounds were isolated. Their structures were elucidated on the basis of spectroscopic evidence. Cytotoxicity against three human cancer cell lines were investigated. Abstract: Six new dammarane-type triterpenes, namely 3β, 6α, 12β-trihydroxy-20 S, 24 S -epoxydammar-25-ene (1 ), 3β-acetoxy-6α, 12β, 25-trihydroxy-24, 25-dihydrodammar-( E )-20(22)-ene (2 ), 3β, 6α, 12β-trihydroxy-20 S, 24 R -epoxydammar-25-ene (3 ), 6α - acetoxy-3β, 12β, 20 R -trihydroxydammar-25-ene (4 ), 6α - acetoxy-3β, 12β, 20 R -trihydroxydammar-24-ene (5 ), and 12β-acetoxy-3β, 6α, 25-trihydroxy-24, 25-dihydrodammar-( E )-20(22)-ene (6 ), together with thirteen known compounds (7–19 ) were isolated from the acidic hydrolysate of the stems-leaves of Panax ginseng . Their chemical structures were elucidated by considerable spectroscopic analyses and comparison with the reported data. All 19 compounds were evaluated for their cytotoxicties against three human cancer cell lines, HL-60, NCI-N87 and Hep-G2. Compound11 exhibited significant inhibitory activity in a concentration-dependent manner against HL-60 and Hep-G2 with the IC50 values of 4.21 and 6.69 μM, respectively. Its activity was stronger than that of the positive control vinorelbine, of which the IC50 values against HL-60 and Hep-G2 were 11.47 and 23.12 μM, respectively. Compounds4, 7, 8, 12–14, and19 showed moderate cytotoxic activities at the concentrations of 1–200 μM against the three human cancer cell lines. The preliminary structure to activity relationship was also discussed based on the experimental data obtained. Complete side chain, the configuration of C-20, the substitution of hydroxyl group of C-25 and C-3 were important factors influencing the cytotoxicities. The results may also provide useful data for researching new anti-tumor agents.